Penerapan E-Commerce Terhadap Kenaikan Pendapatan Usaha Mikro Kecil dan Menengah (Studi Kasus UMKM Bola: V Sport) - Mintawati, Hesri; Simangunsong, Bonse Aris Mandala Putra; Suhardi, Mulyadi; Putri, Dwi Novianti; Salsabilla, Rhaisa; Hariyadi, Septian (JUDICIOUS, 2023)
The main objective of this study is to learn how V Sport and other micro, small, and medium enterprises (MSMEs) in the soccer manufacturing sector use e-commerce to increase their profits. The sources used for this analysis include financial records from Shopee and Lazada Football MSMEs in 2022. In this study, 12 samples were selected for examination using purposive sampling technique. Classical hypothesis testing, multiple linear regression, descriptive analysis, and SPSS hypothesis testing are some of the analytical techniques used. The research shows that Shopee has a great influence on net profit, but Lazada has no real influence. In addition, the study revealed that the combination of Shopee and Lazada significantly increased net profit. An example from MSMEs: V Sport, a soccer ball manufacturer, shows that the combined impact of Shopee and Lazada on net income exceeds the impact generated by any single e-commerce platform.